Mechanical Characteristics of High Plasticity Clay Stabilized Using Lime and Rice Husk Ash - Catur Bejo Santoso; Dora Melati Nurita Sandi; Megalita Rodiyani (G-Tech: Jurnal Teknologi Terapan, 2026)
High-plasticity clay is a type of problematic soil due to its low bearing capacity, low unconfined compressive strength, and high shrinkage-swelling potential. Stabilization is one method for improving the soil's characteristics. The research was conducted through physical property testing of natural soil, including sieve analysis, atterberg limits, moisture content, bulk density, and specific gravity tests, as well as mechanical testing using the UCS method on natural soil and stabilized soil with three mixture variations, namely Variation 1 (5% lime + 4% RHA), Variation 2 (5% lime + 8% RHA), and Variation 3 (5% lime + 12% RHA). The natural soil had an average UCS value of 23.55 kPa, while Variation 1 increased to 95.51 kPa, Variation 2 reached 193.50 kPa, and Variation 3 reached 114.71 kPa. Variation 2 produced the highest UCS value among the variations. The UCS increased by approximately 722% at the optimum mixture of 5% lime + 8% RHA. This study demonstrates that the use of lime and RHA significantly improves the mechanical characteristics of high-plasticity clay.